Learning from halophytes: physiological basis and strategies to improve abiotic stress tolerance in crops - Shabala, Sergey (Annals of botany, 2013)
• Background Global annual losses in agricultural production from salt-affected land are in excess of US$12 billion and rising. At the same time, a significant amount of arable land is becoming lost to urban sprawl, forcing agricultural production into marginal areas. Consequently, there is a need for a major breakthrough in crop breeding for salinity tolerance. Given the limited range of genetic diversity in this trait within traditional crops, stress tolerance genes and mechanisms must be identified in extremophiles and then introduced into traditional crops. • Scope and Conclusions This review argues that learning from halophytes may be a promising way of achieving this goal. The paper is focused around two central questions: what are the key physiological mechanisms conferring salinity tolerance in halophytes that can be introduced into non-halophyte crop species to improve their performance under saline conditions and what specific genes need to be targeted to achieve this goal? The specific traits that are discussed and advocated include: manipulation of trichome shape, size and density to enable their use for external Na⁺ sequestration; increasing the efficiency of internal Na⁺ sequestration in vacuoles by the orchestrated regulation of tonoplast NHX exchangers and slow and fast vacuolar channels, combined with greater cytosolic K⁺ retention; controlling stomata aperture and optimizing water use efficiency by reducing stomatal density; and efficient control of xylem ion loading, enabling rapid shoot osmotic adjustment while preventing prolonged Na⁺ transport to the shoot.